Two different ways of thinking to the eye's direction of gazing - Beronilla, Leyda Escaran (Leyda Escaran Beronilla, 1999)
This study involved 40 qualified college student-participants, twenty (20) left-handed subjects and twenty (20) right-handed subjects who were purposively selected to serve as samples for the whole population. This research was conducted to determine whether left-handed people significantly differ to right-handed people's way of thinking about analytic-verbal and spatial questions using the eye's direction of gazing a clue to determine it. For this research, an interview with each respondent was conducted using six (6) set of questions; three (3) for analytic-verbal type of questions and three (3) for spatial type of questions. Total number of gazes were tallied according to the number of their eye's direction of gazing, either to the left or to the right, and was tabulated to determine the majority to the percentages. Chi-square method was utilized to compute the significant difference between left-handed and right-handed subject's way of thinking. Taken from the distribution of X2, the tabular value of X2 for 1 d.f. at 5% is 3.841. Since the value of 0.1500 is less than 3.841, therefore, this research affirms the null hypothesis of no significant difference between left-handed and right-handed subjects on their two different way of thinking; analytic-verbal and spatial thinking.